ARPC2: A Pan-Cancer Prognostic and Immunological Biomarker That Promotes Hepatocellular Carcinoma Cell Proliferation and Invasion - Huang, Shenglan; Dong, Cairong; Li, Dan; Xu, Yongkang; Wu, Jianbing (Frontiers in Cell and Developmental Biology, 2022)
Background: Actin-related protein 2/3 complex subunit 2 (ARPC2) plays a fundamental role in actin filament nucleation and is critical for tumor cell migration and invasion. However, its abnormal expression, clinical significance, and biological function in human pan-cancer have been poorly explored. Thus, we focused on ARPC2 as an entry point for identifying novel pan-cancer prognostic biomarkers. Methods: The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) databases were used to assess the differential expression of ARPC2 in pan-cancer. The Human Protein Atlas was used for the tissue/cell-specific expression analysis of ARPC2. The genetic alteration information of ARPC2 was obtained from the cBioPortal database and the GSCALite platform. The prognostic value of ARPC2 was explored in pan-cancer using Cox regression and Kaplan-Meier analyses. Spearman correlation analysis was performed to investigate the relationship between ARPC2 expression and tumor mutational burden (TMB), DNA methyltransferases, microsatellite instability (MSI), immune-related genes, and mismatch repairs (MMRs). The ESTIMATE and CIBERSORT algorithms were used to evaluate the association between ARPC2 expression and the tumor microenvironment (TME) and immune infiltrating cells. We also conducted differential expression analysis of ARPC2 in hepatocellular carcinoma (HCC) tissues and cell lines using qPCR, western blotting, and immunohistochemistry and explored its role in tumor proliferation, migration, and invasion of HCC cells. Results: ARPC2 expression was significantly upregulated in multiple tumor types and significantly correlated with worse prognosis and higher clinicopathological stage. Genetic alterations and DNA methylation in tumor tissues may contribute to the aberrant expression of ARPC2. ARPC2 expression was significantly correlated with the TME, infiltrating immune cells, TMB, MSI, and immune checkpoint-related genes in certain cancer types. In this experimental study, we found that the expression of ARPC2 was dramatically upregulated in HCC tissues and cell lines compared to adjacent liver tissues and normal liver cell lines. Functionally, ARPC2 silencing in HCC cells significantly inhibited cell proliferation, migration, and invasion. While overexpression of ARPC2 promotes tumor proliferation, migration, and invasion. Conclusions: ARPC2 is a promising prognostic and immunological biomarker for multiple tumor types and is likely to play an important role in HCC progression and metastasis.